2018
DOI: 10.3390/atmos9020046
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Health Risks of Heavy Metals in PM2.5 in a Campus in a Typical Suburb Area of Taiyuan, North China

Abstract: Abstract:To evaluate air pollution and the public health burden of heavy metals in PM 2.5 in a campus with a population of approximately 40,000 in a typical suburb area of Taiyuan, North China, PM 2.5 measurements were conducted during the spring and winter of 2016. The average concentrations of PM 2.5 in spring and winter were 97.3 ± 35.2 µg m −3 and 205.9 ± 91.3 µg m −3 , respectively. The order of concentration of heavy metals in PM 2.5 was as follows: Zn > Pb > Mn > Cu > Cr > Ni > Cd > As, in both spring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Although ICR values for Cr were reduced from 2006 to 2010/2011, especially for children in JAS (6.1 × 10 −7 ), but Cr remained to pose critical health risk. Similar results have been reported in areas influenced by industrial emissions (Cheng et al, 2017;Liu et al, 2018;Ramírez et al, 2020).…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…Although ICR values for Cr were reduced from 2006 to 2010/2011, especially for children in JAS (6.1 × 10 −7 ), but Cr remained to pose critical health risk. Similar results have been reported in areas influenced by industrial emissions (Cheng et al, 2017;Liu et al, 2018;Ramírez et al, 2020).…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…For example, Li et al [13] measured the economic loss related to health problems due to waste gas emissions and found that the economic loss brought by PM10 and SO 2 accounted for 1.63% and 2.32% of the GDP in 74 cities respectively. Liu et al [14] evaluated the health care burden of waste gas emissions and heavy metals in the spring and winter of 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The higher carcinogenic risk has been found in children and adult for lead (Pb) and Nickel (Ni). Various studies have also reported that the carcinogenic risks by lead exposure exceeded the acceptable level for both children and adult [44][45][46][47]. for resident adult, worker and resident children in Okpella Bua cement production area.…”
Section: Discussionmentioning
confidence: 99%